1992
DOI: 10.1007/bf00920792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha-interferon on gamma-interferon production of peripheral blood mononuclear cells in hepatitis B virus carriers

Abstract: We studied gamma-interferon production of phytohemagglutinin-stimulated peripheral blood mononuclear cells in response to alpha-interferon in hepatitis B virus carriers and healthy individuals. The magnitude of gamma-interferon production was significantly higher in patients with anti-HBe antibody than in patients with HBe antigen and healthy individuals. Furthermore, alpha-interferon augmented the production of gamma-interferon of peripheral blood mononuclear cells from patients with active liver injury [seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…HBV surface antigen (HBsAg), anti-HBV surface antibody (HBsAb) and anti-HCV antibody were measured by the microparticle enzyme immunoassay (MEIA) using the Abbott Axsym System instrument (Abbott Laboratories Ser vices Corporation, Taipei, Taiwan). LD was defined by cutoff > 40 U/L for ALT [14] .…”
Section: Methodsmentioning
confidence: 99%
“…HBV surface antigen (HBsAg), anti-HBV surface antibody (HBsAb) and anti-HCV antibody were measured by the microparticle enzyme immunoassay (MEIA) using the Abbott Axsym System instrument (Abbott Laboratories Ser vices Corporation, Taipei, Taiwan). LD was defined by cutoff > 40 U/L for ALT [14] .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies showed that the production of interferon-? (IFN-y) and monokines is closely associated with clearance of HBV-infected hepatocytes [Muto et al, 1988;Inoue et al, 1989;Daniels et al, 1990;Katayama et al, 1992;Takehara et al, 19921. Based on these findings, IFN-y or tumor necrosis factor-a (TNF-a) was administered to patients with type B chronic hepatitis in several studies.…”
Section: Introductionmentioning
confidence: 99%